2015
DOI: 10.1101/cshperspect.a020552
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaCentral Nervous System Glia

Abstract: Molecular genetic approaches in small model organisms like Drosophila have helped to elucidate fundamental principles of neuronal cell biology. Much less is understood about glial cells, although interest in using invertebrate preparations to define their in vivo functions has increased significantly in recent years. This review focuses on our current understanding of the three major neuron-associated glial cell types found in the Drosophila central nervous system (CNS)-astrocytes, cortex glia, and ensheathing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
308
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(313 citation statements)
references
References 76 publications
(96 reference statements)
3
308
0
2
Order By: Relevance
“…The local control of synapse elimination by microglia relies on the deposition of complement proteins such as C3 and C1q, which are expressed on neurons in an astrocyte-dependent manner, to tag synapses for phagocytosis (Stephan et al, 2012). More recently, it was discovered that astrocytes also directly phagocytose synapses, in both Drosophila and vertebrates, utilizing the Megf10/Draper and Mertk phagocytic receptors (Freeman, 2015;Chung et al, 2015). Mice lacking C1q, or those with astrocytes that lack Megf10 and Mertk, have severe defects in developmental synapse pruning.…”
Section: Synapse Pruning By Gliamentioning
confidence: 99%
“…The local control of synapse elimination by microglia relies on the deposition of complement proteins such as C3 and C1q, which are expressed on neurons in an astrocyte-dependent manner, to tag synapses for phagocytosis (Stephan et al, 2012). More recently, it was discovered that astrocytes also directly phagocytose synapses, in both Drosophila and vertebrates, utilizing the Megf10/Draper and Mertk phagocytic receptors (Freeman, 2015;Chung et al, 2015). Mice lacking C1q, or those with astrocytes that lack Megf10 and Mertk, have severe defects in developmental synapse pruning.…”
Section: Synapse Pruning By Gliamentioning
confidence: 99%
“…For example, many recent studies have shown that astrocytes play important roles in synaptic formation and in modulating the functions of neural circuits and behavior in Drosophila (Zwarts et al, 2015;Freeman, 2015) However, as shown in Fig. 3, the interactions between glia and neurons are ubiquitous throughout the nervous system.…”
Section: Monitoring Interactions Between Glia and Specific Types Of Nmentioning
confidence: 99%
“…The NRR is folded in such a way that, in the absence of Delta binding, a cleavage site (called S2) is inaccessible to the action of ubiquitous metalloproteases such as Kuzbanian (in Drosophila) or TACE (tumor necrosis factor-α-converting enzyme, or ADAM17, in vertebrates) (Tiyanont et al, 2011). Upon Delta-Notch binding, it is hypothesized that the NRR partially unfolds, thereby increasing the accessibility of the S2 site, and the NRR can then be cleaved by the metalloproteases (Stephenson and Avis, 2012;Tiyanont et al, 2011;Meloty-Kapella et al, 2012;2015). After S2 cleavage, a subsequent cleavage (called S3) by the ubiquitous metazoan gamma-secretase complex occurs in the TMD, within the cell membrane (Brou et al, 2000;Mumm et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila neurons share similar processes and morphologies as their mammalian counterpart; they fire proper action potentials, they release conserved neurotransmitters from synaptic vesicles through highly conserved mechanisms, and they pass information between neurons at synapses with common protein architecture [246]. The CNS can be further divided into two histological regions; the neuronal cell cortex -composed of all neuronal cell bodies; and the neuropil -the location of axon and dendrite projection and neural circuit formation [247]. To direct expression of a gene of interest to a specific cell type in Drosophila, the Gal4-UAS system is employed (further described in the methodology, Section; Controlling protein expression: the Gal4-UAS system).…”
Section: Cell Types Of the Nervous System In Drosophilamentioning
confidence: 99%
“…Introduction glial cells have been described from embryonic to adult stage: surface glia -form a layer around the CNS or peripheral nerves; cortex glia -ensheath neuronal cell bodies; and neuropil gliaassociate directly with the neuropil [247], [251]. One of the earliest known markers for cells that will become glia is the transcription factor Reversed polarity (Repo) that is responsible for the differentiation and maintenance of glial cell function.…”
Section: Rna Binding Protein Expressed In Neurons That Is Necessarymentioning
confidence: 99%